The Correlation between English Teachers' Teaching Styles and Students' Grammar Mastery at SMA Pertiwi 1 Padang - Rizka Oktavia Damanik; Aryuliva Adnan (Universitas Negeri Padang, 2023)
Grammar is one of the basics of a language and must be mastered by English students to master English language skills. One of the causes that influence students' grammar mastery is the teacher's teaching style. This research intends to determine the significant relationship between the teaching style of English teachers and students' grammar mastery at SMA Pertiwi 1 Padang. This research used quantitative research with a correlational design. This research involved 80 students of grade 11 and grade 12 of SMA Pertiwi 1 Padang. The instrument of this research was a grammar test and a questionnaire. Based on the questionnaire result, the English teachers used a formal authority style with mean scores of 17.18 and 17.38. Based on the data analysis for the grammar test, it was found that the mean score of students from 11th grade was 34.1, while the mean score of students from 12th grade was 48.1. The researcher found a very high correlation between English teachers' teaching styles and students' grammar mastery. It is proven by rxy (0.995) greater than rtable (0.220). In conclusion, there is a correlation exists between English teachers' teaching styles and students' grammar mastery.